APROKSIMASI KOMPUTASI BAYESIAN: SUATU PENGANTAR - Bertha Selviana Djahi (Jurnal Media Elektro, 2012)
Approximation of Computing Bayesian has many applied in various areas. This method not necessarily calculate function of possibility that as required [by] other Bayesian method like Gibs. This very useful method in inference technique from parameters from a real models complex. This cartridge will study and mereview approximation technique of computing Bayesian and explains two approximation algorithms of computing Bayesian.